MULTIPLEX RT-PCR BASED DETECTION OF HUMAN BOCAVIRUS AND OTHER RESPIRATORY VIRUSES IN INFANTS AND YOUNG CHILDREN WITH LOWER RESPIRATORY TRACT INFECTION (Iraqi Journal of Medical Sciences, 2019)
Background: Human Bocavirus (hBoV) has recently been identified as a causative agent of acute respiratory infection (ARI) in infant and young children. However, there is little information about its frequency and importance as a cause of lower respiratory tract infection (LRTI) in Iraq.Objective:To assess the frequency of hBoV and co-infection rate in infants and young children with LRTI.Methods: Nasopharyngeal/throat swabs were collected during the peak winter months from 100 hospitalized infants and young children less than 5 years of age with LRTI in Baghdad, Iraq. Five viruses were investigated by Multiplex Real-Time Polymerase Chain Reaction (RT-PCR).Results: It was found that 71 (71%) had a viral infection either single or mixed. Six out of 100 samples (6%) were hBoV positive, 10 (10%) were parainfluenza virus positive, 12 (12%) tested positive for adenovirus, 58 (58%) were rhinovirus positive and none of the samples gave positive results for coronavirus. Sixteen samples showed mixed infection with rhinovirus, eight of these (8%) with parainfluenza virus, 6 (6%) with adenovirus, and 2 (2%) with hBoV. There were no significant differences between the viral infected and non-infected patients with respect to age, gender, crowding status, gestational age, diagnosis at presenting and hospital stay (the average stay of viral-infected patients in the hospital was three days). In contrast, exposure to smoking was significantly more associated with viral-infected children than virus-free children (80% vs. 44.83%, P
Keywords: Viral respiratory tract infection; Children; Multiplex Real Time PCR